Solid electrolyte membrane, preparation method thereof and solid-state battery
By introducing polyurethane-based liquid crystal polymers into solid electrolyte membranes, the performance degradation caused by incompatibility of electrolyte membrane materials in traditional solid state batteries is solved, higher ionic conductivity and material toughness are achieved, and the capacity of solid state batteries is improved. and cycle stability.
Patent Information
- Application Number
- CN202411651095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
The organic liquid electrolyte used in traditional lithium metal batteries poses safety risks, and the PVDF-based composite solid electrolyte membrane has a decrease in ionic conductivity and mechanical properties due to incompatibility during the preparation process, which affects the capacity and cycle stability of the solid-state battery.
Polyurethane-based liquid crystal polymer is introduced into the base raw material of the solid electrolyte membrane, and hydrogen bonding is formed through combination with PVDF-based polymer to enhance the dissociation of lithium ions and improve the toughness of the material through the orientation of the liquid crystal polymer.
The ionic conductivity of the composite electrolyte and the toughness of the material are improved, thereby improving the capacity and cycle stability of the solid-state battery.
Smart Images

Figure CN119447426A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte membrane, a preparation method thereof, and a solid-state battery. Background Art
[0002] Traditional lithium metal batteries mostly use organic liquid electrolytes. Due to the thermodynamic instability of lithium metal and the risks of leakage and flammability of liquid electrolytes, traditional lithium-ion batteries face safety risks during application. Solid electrolytes (SSE) have higher safety and are expected to solve the safety problems of liquid electrolytes.
[0003] PVDF-based composite solid electrolyte membrane is a common type of solid electrolyte at present. However, the preparation process of PVDF-based composite solid electrolyte membrane generally involves mixing PVDF, lithium salt and solid electrolyte filler. After compounding with the solid electrolyte filler, the ionic conductivity and mechanical properties of the membrane material decrease due to the incompatibility between the filler and the membrane. This incompatibility results in poor interface adaptability of solid-state batteries and the formation of lithium dendrites, which significantly affects the capacity and cycle stability of solid-state batteries.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a solid electrolyte membrane, a preparation method thereof and a solid-state battery, aiming to improve the capacity and cycle stability of the solid-state battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a solid electrolyte membrane, comprising a basic raw material and a polyurethane-based liquid crystal polymer, wherein the basic raw material comprises 20%-80% of a PVDF-based polymer, 10%-50% of a lithium salt and 5%-30% of a solid electrolyte in terms of mass percentage;
[0008] Wherein, the mass ratio of polyurethane-based liquid crystal polymer to PVDF-based polymer is (1-10):100;
[0009] The molecular structure of polyurethane-based liquid crystal polymer is:
[0010]
[0011] In an optional embodiment, the basic raw material includes, by mass percentage, 30%-40% lithium salt, 40%-60% PVDF-based polymer, and 20%-30% solid electrolyte.
[0012] In an optional embodiment, the mass ratio of the polyurethane-based liquid crystal polymer to the PVDF-based polymer is (3-8): 100;
[0013] Preferably, the mass ratio of the polyurethane-based liquid crystal polymer to the PVDF-based polymer is (4-7):100.
[0014] In an alternative embodiment, the PVDF-based polymer is polyvinylidene fluoride-hexafluoropropylene.
[0015] In an alternative embodiment, the lithium salt is selected from at least one of LiTFSI, LiFSI and LiDFOB.
[0016] In an optional embodiment, the solid electrolyte is selected from at least one of LATP, LLZO and LLTO.
[0017] In a second aspect, the present invention provides a method for preparing a solid electrolyte membrane according to any one of the aforementioned embodiments, comprising: mixing a polyurethane-based liquid crystal polymer and each component in a basic raw material according to a ratio.
[0018] In an optional embodiment, a polyurethane-based liquid crystal polymer, a PVDF-based polymer and a dispersant are mixed to obtain a first mixture, the first mixture and a lithium salt are mixed to obtain a second mixture, the second mixture and a solid electrolyte are mixed to obtain a mixed slurry, and the mixed slurry is coated and dried;
[0019] Preferably, the dispersant is selected from at least one of N-methylpyrrolidone and dimethylformamide;
[0020] In the process of preparing the first mixture, the second mixture and the mixed slurry, the mixing temperature is controlled to be 20° C.-70° C.;
[0021] The coating temperature is controlled at 80°C-130°C and the scraper speed is controlled at 20mm / s-80mm / s.
[0022] In an optional embodiment, the preparation process of the polyurethane-based liquid crystal polymer is as follows: 6-chloro-1-hexanol, 4,4'-hydroxybiphenol and an organic solvent are mixed to obtain a reaction mixture, sodium hydroxide and the organic solvent are mixed to obtain an alkaline reaction solution, the reaction mixture is added dropwise to the alkaline reaction solution, and the reaction is carried out at 75° C. to 80° C. for 10 h to 15 h to obtain an intermediate product BP6;
[0023] The intermediate product BP6 is mixed with hexamethylene diisocyanate and an organic solvent, and reacted in the presence of dibutyltin dilaurate, with the reaction temperature controlled at 85°C-95°C and the reaction time at 20h-30h;
[0024] Preferably, the molar ratio of 6-chloro-1-hexanol to 4,4'-p-hydroxybiphenol is 0.1:(0.03-0.07);
[0025] The molar ratio of the intermediate product BP6 to hexamethylene diisocyanate is 1:(1.00-1.03);
[0026] The added amount of dibutyltin dilaurate is 2.5%-3.5% of the total mass of the intermediate product BP6 and hexamethylene diisocyanate.
[0027] In a third aspect, the present invention provides a solid-state battery, comprising a solid-state electrolyte membrane according to any one of the aforementioned embodiments or a solid-state electrolyte membrane prepared by any one of the preparation methods according to the aforementioned embodiments.
[0028] The present invention has the following beneficial effects: the present invention introduces a specific type of polyurethane-based liquid crystal polymer into the electrolyte membrane, which has the urethane ester and rigid liquid crystal unit unique to the polyurethane resin, and can form hydrogen bonds with lithium salt anions, thereby enhancing the dissociation of lithium ions, thereby improving the ionic conductivity of the composite electrolyte. At the same time, after the liquid crystal polymer is heated to the melting point, it has good fluidity, can be oriented into fibers under the action of external forces, improves the toughness of the material, and is conducive to ensuring the capacity and cycle stability of the solid-state battery.
[0029] It should be added that during the preparation process, the polyurethane-based liquid crystal polymer is compounded with the PVDF-based formula, the coating temperature is controlled to make the liquid crystal polymer in a liquid crystal state, and then the coating parameters are controlled to orient the liquid crystal polymer into fibers. The structure is retained after drying, thereby achieving the effect of toughening and improving ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 The cross-sectional morphology of the composite solid electrolyte; (a) indicates no LCPU is added; (b) indicates the addition of LCPU;
[0032] Figure 2 This is the ionic conductivity test result diagram;
[0033] Figure 3 This is a graph showing the cycle performance test results. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] An embodiment of the present invention provides a solid electrolyte membrane, including a basic raw material and a polyurethane-based liquid crystal polymer. A specific type of polyurethane-based liquid crystal polymer is added to the basic raw material of the solid electrolyte membrane. The molecular structure of the polyurethane-based liquid crystal polymer is as follows:
[0036]
[0037] It should be noted that the unique carbamate and rigid liquid crystal unit (i.e. biphenyl group) of the polyurethane-based liquid crystal polymer can form hydrogen bonds with the amide bond and lithium salt anion, thereby enhancing the dissociation of lithium ions and improving the ionic conductivity of the composite electrolyte. At the same time, after the liquid crystal polymer is heated to the melting point, it has good fluidity and can be oriented into fibers under the action of external forces, which improves the toughness of the material and is conducive to ensuring the capacity and cycle stability of the solid-state battery.
[0038] In some embodiments, the basic raw materials include 20%-80% PVDF-based polymer, 10%-50% lithium salt and 5%-30% solid electrolyte by mass percentage; the mass ratio of polyurethane-based liquid crystal polymer to PVDF-based polymer is (1-10): 100. The amount of polyurethane-based liquid crystal polymer is preferably within the above range to further improve the ionic conductivity of the composite electrolyte.
[0039] Specifically, in the basic raw materials, the mass fraction of PVDF-based polymer can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, etc.; the mass fraction of lithium salt can be 10%, 20%, 30%, 40%, 50%, etc., and the mass fraction of solid electrolyte can be 5%, 10%, 15%, 20%, 25%, 30%, etc. The mass ratio of polyurethane-based liquid crystal polymer to PVDF-based polymer can be 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, etc.
[0040] In a preferred embodiment, the basic raw material includes 30%-40% lithium salt, 40%-60% PVDF-based polymer and 20%-30% solid electrolyte by mass percentage. The composition of the basic raw material is preferably within the above range, which is conducive to further improving the conductive properties of the solid electrolyte membrane.
[0041] In a preferred embodiment, the mass ratio of the polyurethane-based liquid crystal polymer to the PVDF-based polymer is (3-8): 100, more preferably (4-7): 100. It is preferable to control the amount of the polyurethane-based liquid crystal polymer within the above range, which can further enhance the dissociation of lithium ions and improve the ionic conductivity of the composite electrolyte membrane itself.
[0042] In some embodiments, the PVDF-based polymer is polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), which can be commercially available, such as from Shanghai Aladdin Biochemical Technology Co., Ltd. with company model number P304908.
[0043] In some embodiments, the lithium salt is selected from at least one of LiTFSI, LiFSI and LiDFOB, and the lithium salt can be any one or more of the above. The solid electrolyte is selected from at least one of LATP (lithium aluminum titanium phosphate), LLZO (lithium lanthanum zirconium oxide) and LLTO (lithium lanthanum titanium oxide), and the above solid electrolytes are all commercially available raw materials, and the solid electrolyte can be any one or more of the above.
[0044] The present invention provides a method for preparing a solid electrolyte membrane, the steps of which are as follows:
[0045] (1) Providing polyurethane-based liquid crystal polymers
[0046] The preparation process of the polyurethane-based liquid crystal polymer LCPU provided in the embodiment of the present invention is as follows:
[0047]
[0048] The preparation process of polyurethane-based liquid crystal polymer is as follows:
[0049] The first step of the reaction is to mix 6-chloro-1-hexanol, 4,4'-p-hydroxybiphenol and an organic solvent to obtain a reaction mixture, mix sodium hydroxide and an organic solvent to obtain an alkaline reaction solution, dropwise add the reaction mixture into the alkaline reaction solution, and react at 75° C.-80° C. for 10 h-15 h to obtain an intermediate product BP6; the molar ratio of 6-chloro-1-hexanol to 4,4'-p-hydroxybiphenol is 0.1:(0.03-0.07);
[0050] The second step reaction: the intermediate product BP6 is mixed with hexamethylene diisocyanate and an organic solvent, and the reaction is carried out in the presence of dibutyltin dilaurate, the reaction temperature is controlled to be 85°C-95°C, and the reaction time is 20h-30h; the molar ratio of the intermediate product BP6 to hexamethylene diisocyanate is 1:(1.00-1.03); the amount of dibutyltin dilaurate added is 2.5%-3.5% of the total mass of the intermediate product BP6 and hexamethylene diisocyanate.
[0051] The specific steps are as follows: dissolve 0.1 mol of sodium hydroxide in 20 ml of anhydrous ethanol, heat the oil bath to 50 ° C and stir, fully dissolve 6-chloro-1-hexanol and 4,4'-hydroxybiphenol in a molar ratio of 0.1:0.05 with 50 mL of anhydrous ethanol in an ultrasonic disperser, and slowly add it to the sodium hydroxide solution. After the addition is completed, heat to 78 ° C and react for 12 hours to obtain the intermediate product BP6. Dissolve BP6 and HDI in DMF solvent at a molar ratio of 1:1.01, heat to 60 ° C and disperse evenly, add catalyst dibutyltin dilaurate (DBTL) at 3wt% of the total mass, and react at 90 ° C for 24 hours to obtain the target product LCPU.
[0052] LCPU can be prepared through two-step reaction, which is simple, easy and convenient to operate.
[0053] (2) Mixing and coating
[0054] The polyurethane-based liquid crystal polymer and the components in the basic raw materials are evenly mixed according to the ratio, and then prepared into a solid electrolyte membrane.
[0055] In some embodiments, a polyurethane-based liquid crystal polymer, a PVDF-based polymer and a dispersant are mixed to obtain a first mixture, the first mixture is mixed with a lithium salt to obtain a second mixture, the second mixture is mixed with a solid electrolyte to obtain a mixed slurry, and the mixed slurry is coated and dried. By adjusting the mixing order, the polyurethane-based liquid crystal polymer and the lithium salt can work better; the coating method is used to prepare the film, and the polyurethane liquid crystal polymer is oriented into fibers when the composite electrolyte membrane is coated, thereby achieving toughening of the membrane material.
[0056] In some embodiments, the dispersant is selected from at least one of N-methylpyrrolidone (NMP) and dimethylformamide (DMF). The dispersant may be any one or more of the above, which can further improve the uniformity of the mixed slurry.
[0057] In some embodiments, during the preparation of the first mixture, the second mixture and the mixed slurry, the mixing temperature is controlled to be 20°C-70°C, the overall stirring time can be 0.5h-3.0h, and the stirring speed can be 300rpm-800rpm, so that the components are fully mixed. Specifically, the mixing process can be carried out under water bath heating conditions, and the heating temperature can be controlled to be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, etc.
[0058] In some embodiments, the coating temperature is controlled to be 80°C-130°C, and the scraper speed is 20mm / s-80mm / s. By controlling the coating temperature, the liquid crystal polymer is in a liquid crystal state, and then the coating parameters are controlled to orient the liquid crystal polymer into fibers, and the structure is retained after drying, thereby achieving the effect of toughening and improving ionic conductivity. Specifically, the coating temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, etc.; the scraper speed can be 20mm / s, 30mm / s, 40mm / s, 50mm / s, 60mm / s, 70mm / s, 80mm / s, etc.
[0059] An embodiment of the present invention further provides a solid-state battery, including a solid-state electrolyte membrane, and may also include a positive electrode and a negative electrode, wherein the solid-state electrolyte membrane is disposed between the positive electrode and the negative electrode to form a complete solid-state battery structure.
[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0061] Example 1
[0062] This embodiment provides a method for preparing a solid electrolyte membrane, the steps are as follows:
[0063] (1) Preparation of polyurethane-based liquid crystal polymer LCPU, the preparation process is as follows:
[0064]
[0065] The specific steps are as follows: 0.1 mol of sodium hydroxide is dissolved in 20 ml of anhydrous ethanol, the oil bath is heated to 50°C and stirred, 0.1 mol of 6-chloro-1-hexanol and 0.05 mol of 4,4'-hydroxybiphenol and 50 mL of anhydrous ethanol are fully dissolved in an ultrasonic disperser, and slowly added to the sodium hydroxide solution. After the addition is completed, the temperature is raised to 78°C and reacted for 12 hours to obtain the intermediate product BP6. 0.1 mol of BP6 and 0.101 mol of HDI are dissolved in 100 mL of DMF solvent, the temperature is raised to 60°C and dispersed evenly, the catalyst dibutyltin dilaurate (DBTL) is added according to 3 wt% of the total mass (i.e. the total amount of BP6 and HDI), the reaction is carried out at 90°C for 24 hours, 100 mL of methanol is added to quench the reaction, and the target product LCPU is obtained after filtration and drying.
[0066] (2) Preparation of materials
[0067] A basic raw material is prepared. The basic raw material includes, by mass percentage, 50% of a PVDF-based polymer (PVDF-HFP), 30% of LiTFSI, and 20% of LATP.
[0068] Specifically, the mass of PVDF-HFP is 0.5 g, the mass of LiTFSI is 0.3 g, and the mass of LATP is 0.2 g; the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 5:100.
[0069] (3) Mixing and coating
[0070] The polyurethane-based liquid crystal polymer, the PVDF-based polymer and 4 mL of NMP were mixed to obtain a first mixture, the first mixture was mixed with LiTFSI to obtain a second mixture, the second mixture was mixed with LATP to obtain a mixed slurry, the scraper thickness was adjusted to 100 μm, the mixed slurry was coated on an aluminum foil, and then dried.
[0071] In the process of preparing the first mixture, the second mixture and the mixed slurry, the mixing temperature is controlled to be 40°C, the mixing time of each step is 1 hour, and the stirring speed can be 600 rpm. The coating temperature is controlled to be 100°C, the scraper speed is 40 mm / s, the drying temperature is 80°C, and the drying time is 12 hours.
[0072] Example 2
[0073] The only difference from Example 1 is that the amount of each component in step (2) is calculated by mass percentage, and the basic raw material includes 80% of PVDF-based polymer (PVDF-HFP), 10% of LiTFSI and 10% of LATP. Specifically, the mass of PVDF-HFP is 0.8g, the mass of LiTFSI is 0.1g, and the mass of LATP is 0.1g; the mass ratio of polyurethane-based liquid crystal polymer LCPU to PVDF-based polymer is 5:100.
[0074] Example 3
[0075] The only difference from Example 1 is that the amount of each component in step (2) is calculated by mass percentage, and the basic raw material includes 20% PVDF-based polymer (PVDF-HFP), 50% LiTFSI and 30% LATP. Specifically, the mass of PVDF-HFP is 0.2g, the mass of LiTFSI is 0.5g, and the mass of LATP is 0.3g; the mass ratio of polyurethane-based liquid crystal polymer LCPU to PVDF-based polymer is 5:100.
[0076] Example 4
[0077] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 1:100.
[0078] Example 5
[0079] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 3:100.
[0080] Example 6
[0081] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 7:100.
[0082] Example 7
[0083] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 10:100.
[0084] Comparative Example 1
[0085] The only difference from Example 1 is that polyurethane-based liquid crystal polymer LCPU is not added in steps (2) and (3).
[0086] Comparative Example 2
[0087] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 0.1:100.
[0088] Comparative Example 3
[0089] The only difference from Example 1 is that the mass ratio of the polyurethane-based liquid crystal polymer LCPU to the PVDF-based polymer is 15:100.
[0090] Comparative Example 4
[0091] The only difference from Example 1 is that the polyurethane-based liquid crystal polymer LCPU is replaced by HDI-type TPU, which is synthesized using PEG-1000 and HDI, and the synthesis method is the same as that of LCPU.
[0092] Comparative Example 5
[0093] The only difference from Example 1 is that the polyurethane-based liquid crystal polymer LCPU is replaced by IPDI-type TPU, which is synthesized using PEG-1000 and IPDI in the same synthesis method as LCPU.
[0094] Test example
[0095] (1) The cross-sectional morphology of the solid electrolyte membrane prepared in Example 1 and Comparative Example 1 is as follows: Figure 1 As shown, (a) indicates that no LCPU is added, and (b) indicates that an LCPU is added.
[0096] from Figure 1It can be seen that the electrolyte membrane obtained after adding LCPU is denser than that without adding LCPU, and there are no obvious pores on the surface. At the same time, there is no phase separation with the polymer matrix, and the two have good compatibility.
[0097] (2) The ionic conductivity of the solid electrolyte membranes prepared in Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 2 The test conditions are as follows: the ambient temperature is 25°C, the composite solid electrolyte membrane is sandwiched between stainless steel disk electrodes (SS), the ionic conductivity is measured by electrochemical impedance spectroscopy in the frequency range of 0.1Hz-1MHz and the AC amplitude is 10mV.
[0098] from Figure 2 It can be seen that in Comparative Example 1, LCPU was not added, and the ionic conductivity of the obtained solid electrolyte membrane was 1.9*10 -5 S / cm; Example 1 adds LCPU, and the ionic conductivity of the obtained solid electrolyte membrane is 3.1*10 -5 S / cm.
[0099] (3) The solid electrolyte membranes prepared in the examples and comparative examples were assembled into solid-state batteries, and their capacity cycle performance was tested. The results are shown in Tables 1 and Figure 3 shown.
[0100] Test method: Use NCM811 positive electrode sheet with surface loading of 2.5mg / cm2 as positive electrode, stack composite solid electrolyte membrane and lithium sheet on the positive electrode, and assemble CR2025 type buckle battery after adding gasket and spring. At 55℃, charge and discharge at 0.05C rate, and cycle 50 times at 0.1C.
[0101] Table 1 Capacity and cycle performance test results
[0102]
[0103] It can be seen from Table 1 that, by adding LCPU, the solid electrolyte membrane prepared in the present invention has higher ionic conductivity during application, which is beneficial to improving the capacity and cycle performance of the solid-state battery.
[0104] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solid electrolyte membrane, characterized in that: It includes basic raw materials and polyurethane-based liquid crystal polymers. In terms of mass percentage, the basic raw materials include 20%-80% of PVDF-based polymers, 10%-50% of lithium salts and 5%-30% of solid electrolytes. Wherein, the mass ratio of polyurethane-based liquid crystal polymer to PVDF-based polymer is (1-10):100; The molecular structure of the polyurethane-based liquid crystal polymer is:
2. The solid electrolyte membrane according to claim 1, characterized in that Calculated by mass percentage, the basic raw material includes 30%-40% lithium salt, 40%-60% PVDF-based polymer and 20%-30% solid electrolyte.
3. The solid electrolyte membrane according to claim 1 or 2, characterized in that: The mass ratio of the polyurethane-based liquid crystal polymer to the PVDF-based polymer is (3-8): 100; Preferably, the mass ratio of the polyurethane-based liquid crystal polymer to the PVDF-based polymer is (4-7):
100.
4. The solid electrolyte membrane according to claim 1, characterized in that The PVDF-based polymer is polyvinylidene fluoride-hexafluoropropylene.
5. The solid electrolyte membrane according to claim 1, characterized in that ,, the lithium salt is selected from at least one of LiTFSI, LiFSI and LiDFOB.
6. The solid electrolyte membrane according to claim 1, characterized in that The solid electrolyte is selected from at least one of LATP, LLZO and LLTO.
7. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: include: The polyurethane-based liquid crystal polymer and the components in the basic raw materials are mixed according to a ratio.
8. The preparation method according to claim 7, characterized in that: The polyurethane-based liquid crystal polymer, the PVDF-based polymer and a dispersant are mixed to obtain a first mixture, the first mixture is mixed with the lithium salt to obtain a second mixture, the second mixture is mixed with the solid electrolyte to obtain a mixed slurry, and the mixed slurry is coated and dried; Preferably, the dispersant is selected from at least one of N-methylpyrrolidone and dimethylformamide; In the process of preparing the first mixture, the second mixture and the mixed slurry, the mixing temperature is controlled to be 20° C.-70° C.; The coating temperature is controlled at 80°C-130°C and the scraper speed is controlled at 20mm / s-80mm / s.
9. The preparation method according to claim 8, characterized in that: The preparation process of the polyurethane-based liquid crystal polymer is as follows: 6-chloro-1-hexanol, 4,4'-hydroxybiphenol and an organic solvent are mixed to obtain a reaction mixture, sodium hydroxide and an organic solvent are mixed to obtain an alkaline reaction solution, the reaction mixture is added dropwise to the alkaline reaction solution, and the reaction is carried out at 75° C. to 80° C. for 10 h to 15 h to obtain an intermediate product BP6; The intermediate product BP6 is mixed with hexamethylene diisocyanate and an organic solvent, and reacted in the presence of dibutyltin dilaurate, with the reaction temperature being controlled at 85° C.-95° C. and the reaction time being 20 h-30 h; Preferably, the molar ratio of 6-chloro-1-hexanol to 4,4'-p-hydroxybiphenol is 0.1:(0.03-0.07); The molar ratio of the intermediate product BP6 to hexamethylene diisocyanate is 1:(1.00-1.03); The added amount of dibutyltin dilaurate is 2.5%-3.5% of the total mass of the intermediate product BP6 and hexamethylene diisocyanate.
10. A solid-state battery, characterized in that: The invention comprises the solid electrolyte membrane described in any one of claims 1 to 6 or the solid electrolyte membrane prepared by the preparation method described in any one of claims 7 to 9.